Differential dynamics of the serotonin(1A) receptor in membrane bilayers of varying cholesterol content revealed by all atom molecular dynamics simulation - Patra, Swarna M.; Chakraborty, Sudip; Shahane, Ganesh; Prasanna, Xavier; Sengupta, Durba; Maiti, Prabal K.; Chattopadhyay, Amitabha (Molecular Membrane Biology, 2015)
The serotonin(1A) receptor belongs to the superfamily of G protein-coupled receptors (GPCRs) and is a potential drug target in neuropsychiatric disorders. The receptor has been shown to require membrane cholesterol for its organization, dynamics and function. Although recent work suggests a close interaction of cholesterol with the receptor, the structural integrity of the serotonin(1A) receptor in the presence of cholesterol has not been explored. In this work, we have carried out all atom molecular dynamics simulations, totaling to 3s, to analyze the effect of cholesterol on the structure and dynamics of the serotonin(1A) receptor. Our results show that the presence of physiologically relevant concentration of membrane cholesterol alters conformational dynamics of the serotonin(1A) receptor and, on an average lowers conformational fluctuations. Our results show that, in general, transmembrane helix VII is most affected by the absence of membrane cholesterol. These results are in overall agreement with experimental data showing enhancement of GPCR stability in the presence of membrane cholesterol. Our results constitute a molecular level understanding of GPCR-cholesterol interaction, and represent an important step in our overall understanding of GPCR function in health and disease.
Keywords: GPCR; Membrane cholesterol; molecular dynamics simulation; serotonin(1A) receptor

Molecular dynamics simulations of GPCR-cholesterol interaction: an emerging paradigm - Sengupta, Durba; Chattopadhyay, Amitabha (Biochimica Et Biophysica Acta-Biomembranes, 2015)
G protein-coupled receptors (GPCRs) are the largest class of molecules involved in signal transduction across cell membranes and represent major targets in the development of novel drug candidates. Membrane cholesterol plays an important role in GPCR structure and function. Molecular dynamics simulations have been successful in exploring the effect of cholesterol on the receptor and a general consensus molecular view is emerging. We review here recent molecular dynamics studies at multiple resolutions highlighting the main features of cholesterol-GPCR interaction. Several cholesterol interaction sites have been identified on the receptor that are reminiscent of nonannular sites. These cholesterol hot-spots are highly dynamic and have a microsecond time scale of exchange with the bulk lipids. A few consensus sites (such as the CRAC site) have been identified that correspond to higher cholesterol interaction. Interestingly, high plasticity is observed in the modes of cholesterol interaction and several sites have been suggested to have high cholesterol occupancy. We therefore believe that these cholesterol hot-spots are indicative of `high occupancy sites' rather than `binding sites'. The results suggest that the energy landscape of cholesterol association with GPCRs corresponds to a series of shallow minima interconnected by low barriers. These specific interactions, along with general membrane effects, have been observed to modulate GPCR organization. Membrane cholesterol effects on receptor structure and organization, that in turn influences receptor cross-talk and drug efficacy, represent a new frontier in GPCR research. This article is part of a Special Issue entitled: Lipid-protein interactions. Guest Editors: Amitabha Chattopadhyay and jean-Marie Ruysschaert. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Coarse-grain simulation; CRAC; GPCR; Lipid-receptor interaction; Membrane cholesterol; Receptor dimerization

Differential dynamics underlying the Gln27Glu population variant of the beta(2)-adrenergic receptor - Bhosale, Sumedha; Nikte, V. Siddhanta; Sengupta, Durba; Joshi, Manali (Journal of Membrane Biology, 2019)
The beta (2)-adrenergic receptor (beta (2)AR) is a membrane-bound G-protein-coupled receptor and an important drug target for asthma. Clinical studies report that the population variant Gln27Glu is associated with a differential response to common asthma drugs, such as albuterol, isoproterenol and terbutaline. Interestingly, the 27th amino acid is positioned on the N-terminal region that is the most flexible and consequently the least studied part of the receptor. In this study, we probe the molecular origin of the differential drug binding by performing structural modeling and simulations of the wild-type (Gln) and variant (Glu) receptors followed by ensemble docking with the ligands, albuterol, isoproterenol and terbutaline. In line with clinical studies, the ligands were observed to interact preferentially with the Glu variant. Our results indicate that the Glu residue at the 27th position perturbs the network of electrostatic interactions that connects the N-terminal region to the binding site in the wild-type receptor. As a result, the Glu variant is observed to bind better to the three ligands tested in this study. Our study provides a structural basis to explain the variable drug response associated with the 27th position polymorphism in the beta (2)AR and is a starting step to identify genotype-specific therapeutics.
Keywords: beta(2)-Adrenergic receptor; G-protein-coupled receptor; GPCR; molecular dynamics; Pharmacogenetics; SNP

Loss of a water-mediated network results in reduced agonist affinity in a beta(2)-adrenergic receptor clinical variant - Nikte, V. Siddhanta; Sonar, Krushna; Tandale, Aditi; Joshi, Manali; Sengupta, Durba (Biochimica ET Biophysica Acta-Proteins and Proteomics, 2021)
The beta(2)-adrenergic receptor (beta(2)AR) is a member of the G protein-coupled receptor (GPCR) family that is an important drug target for asthma and COPD. Clinical studies coupled with biochemical data have identified a critical receptor variant, Thr164Ile, to have a reduced response to agonist-based therapy, although the molecular mechanism underlying this seemingly ``non-deleterious'' substitution is not clear. Here, we couple molecular dynamics simulations with network analysis and free-energy calculations to identify the molecular determinants underlying the differential drug response. We are able to identify hydration sites in the transmembrane domain that are essential to maintain the integrity of the binding site but are absent in the variant. The loss of these hydration sites in the variant correlates with perturbations in the intra-protein interaction network and rearrangements in the orthosteric ligand binding site. In conjunction, we observe an altered binding and reduced free energy of a series of agonists, in line with experimental trends. Our work identifies a functional allosteric pathway connected by specific hydration sites in beta(2)AR that has not been reported before and provides insight into water-mediated networks in GPCRs in general. Overall, the work is one of the first step towards developing variant-specific potent and selective agonists.
Keywords: beta(2)-Adrenergic receptor; G protein coupled receptor; GPCR; molecular dynamics; Pharmacogenetics; SNP

Synergistic and competitive lipid interactions in the serotonin1A receptor microenvironment - Mohole, Madhura; Sengupta, Durba; Chattopadhyay, Amitabha (ACS Chemical Neuroscience, 2022)
The interaction of lipids with G-protein-coupled receptors (GPCRs) has been shown to modulate and dictate several aspects of GPCR organization and function. Diverse lipid interaction sites have been identified from structural biology, bioinformatics, and molecular dynamics studies. For example, multiple cholesterol interaction sites have been identified in the serotonin1A receptor, along with distinct and overlapping sphingolipid interaction sites. How these lipids interact with each other and what is the resultant effect on the receptor is still not clear. In this work, we have analyzed lipid-lipid crosstalk at the receptor of the serotonin1A receptor embedded in a membrane bilayer that mimics the neuronal membrane composition by long coarse-grain simulations. Using a set of similarity coefficients, we classified lipids that bind at the receptor together as synergistic cobinding, and those that bind individually as competitive. Our results show that certain lipids interact with the serotonin1A receptor in synergy with each other. Not surprisingly, the ganglioside GM1 and cholesterol show a synergistic cobinding, along with the relatively uncommon GM1-phosphatidylethanolamine (PE) and cholesterol-PE synergy. In contrast, certain lipid pairs such as cholesterol and sphingomyelin appear to be in competition at several sites, despite their coexistence in lipid nanodomains. In addition, we observed intralipid competition between two lipid tails, with the receptor exhibiting increased interactions with the unsaturated lipid tails. We believe our work represents an important step in understanding the diversity of GPCR-lipid interactions and exploring synergistic cobinding and competition in natural membranes.
Keywords: GPCR; lipid crosstalk; Martini coarse-grain simulations; Membrane cholesterol; neuronal membranes

State-dependent dynamics of extramembrane domains in the β2-adrenergic receptor - Nikte, Siddhanta V.; Joshi, Manali; Sengupta, Durba (Proteins- Structure Function and Bioinformatics, 2024)
G protein-coupled receptors (GPCRs) are membrane-bound signaling proteins that play an essential role in cellular signaling processes. Due to their intrinsic function of transmitting internal signals in response to external cues, these receptors are adapted to be highly dynamic in nature. The beta(2)-adrenergic receptor (beta 2AR) is a representative member of the family that has been extensively analyzed in terms of its structure and activation. Although the structure of the transmembrane domain has been characterized in the different functional states of the receptor, the conformational dynamics of the extramembrane domains, especially the intrinsically disordered regions are still emerging. In this study, we analyze the state-dependent dynamics of extramembrane domains of beta(2)AR using atomistic molecular dynamics simulations. We introduce a parameter, the residue excess dynamics that allows us to better quantify receptor dynamics. Using this measure, we show that the dynamics of the extramembrane domains are sensitive to the receptor state. Interestingly, the ligand-bound intermediate R' state shows the maximal dynamics compared to either the active R*G or inactive R states. Ligand binding appears to be correlated with high residue excess dynamics that are dampened upon G protein coupling. The intracellular loop-3 (ICL3) domain has a tendency to flip towards the membrane upon ligand binding, which could contribute to receptor ``priming.'' We highlight an important ICL1-helix-8 interplay that is broken in the ligand-bound state but is retained in the active state. Overall, our study highlights the importance of characterizing the functional dynamics of the GPCR loop domains.
Keywords: allosteric pathway; beta-2 adrenergic receptor; extramembrane domains; GPCR; loop dynamics; protein dynamics; protein network

Specificity and promiscuity of phosphoinositide lipid interactions with the serotonin1A receptor: insights from submillisecond coarse-grain simulations - Nikte, Siddhanta V.; Sengupta, Durba; Chattopadhyay, Amitabha (ACS Chemical Neuroscience, 2026)
G protein-coupled receptors (GPCRs) are lipid-dependent membrane receptors that serve as important cell signaling hubs. Phosphoinositide (PIP) lipids represent an important class of anionic lipids that play vital roles in neuronal function and signaling. PIP lipids have been reported to modulate GPCR function, although the specificity and molecular details of the interactions are still not clear. An important GPCR in this context is the serotonin(1A) receptor, a neurotransmitter GPCR, which has been reported to interact with phosphatidylinositol 4-phosphate (PIP1) lipids. In this work, we computationally analyzed the specificity of the serotonin(1A) receptor-PIP lipid interactions using coarse-grain molecular dynamics simulations. Our results predict that four anionic lipid sites are present at the receptor surface, although the relative populations are dependent on the lipid type. PIP1 lipids exhibit the highest interaction at a charged cleft formed by transmembrane helices VI and VII. We observed electrostatic interactions at a cluster of charged residues (Arg341, Lys342, Lys345) and hydrophobic and aromatic interactions at residue Ile349 and Tyr402. In contrast, phosphatidylinositol 4,5-bisphosphate (PIP2) and phosphatidylinositol 3,4,5-trisphosphate (PIP3) lipids interact more with transmembrane helix IV. We observed that anionic phospholipids such as phosphatidylserine (PS) interact at these sites, although their occupancy at these sites is much reduced. By elucidating the molecular determinants of these interactions in silico, this study generates novel, testable hypotheses regarding the functional role of specific lipid-receptor contacts. Our work constitutes an important step in analyzing molecular signatures of phosphoinositide lipid-GPCR interactions in the overall context of diverse roles of phosphoinositides in neuronal function and signaling.
Keywords: anionic lipids; Cholesterol; GPCR; MARTINIcoarse-grain simulations; PIP lipids; serotonin(1A) receptor